The rise of hybrid actors in the Asia-Pacific. - Ong, Weichong (Pacific Review, 2018)
This article examines the manifestation and trends of hybrid warfare in the Asia-Pacific region through the lenses of the following three key hybrid actors: China, North Korea and ISIS affiliates in Southeast Asia. This article explains why the hybrid approach can be such an attractive strategic option for both state and non-state actors in the Asia-Pacific. Finally, this paper will address the impact of how the constant pushing of boundaries in hybrid warfare can lead to unintended consequences.